Development of best practice recommendations to enhance access to and use of formal community care services for people with dementia in Europe: a Delphi process conducted by the Actifcare project. (2nd December 2021) - Røsvik, Janne; Michelet, Mona; Engedal, Knut; Bergh, Sverre; Bieber, Anja; Gonçalves-Pereira, Manuel; Portolani, Daniel Michael; Hopper, Louise; Irving, Kate; Jelley, Hannah; Kerpershoek, Liselot; Meyer, Gabriele; et al.
Abstract: Objectives: Home-dwelling people with dementia and their informal carers experience barriers impeding access to community care services. This study is a part of the Actifcare project where eight countries participated. The aim was to achieve consensus on best practice recommendations for enhancing access to and use of formal community care services. Method: A Delphi consensus process was conducted. A total of 48 professional experts, 14 people with dementia and 20 informal carers rated the importance of 72 statements on a 7-point Likert scale. Consensus was based on the median and level of dispersion. Results: Sixty-two statements reached consensus, resulting in three categories of recommendations. An appointed contact person was central in Recommendations to enhance access . Coordination and flexibility in setting and type of services were among the Recommendations to enhance use . Training of health care personnel and person-centred care were central Recommendations that can facilitate access or use indirectly . Conclusion: The Actifcare Best Practice Recommendations suggest practical measures that can be taken by decision makers to enhance access and use of community care services, and thereby enhance quality of care and quality of life for home dwelling people with dementia and their informal carers.